Digitization of Legal Philosophy from a Postmodernism Perspective - Hyronimus Rhiti; Vincentius Patria Setyawan (Jurnal Kewarganegaraan, 2020)
Abstract Digitalization in the era of the industrial revolution 4.0 also had an impact on the development of legal philosophy, especially towards postmodernism. The process of digitizing the modern world seems to have become a culture of all aspects of life which includes laws that are constantly developing towards post-modernity (after modernity). This article aims to explore the influence of the digitalization phenomenon on the development of legal philosophy, especially the postmodern school. This article is written using a normative legal research method with a conceptual approach. Data collection was carried out by means of a literature study. The results of the research in this article show that the development of the postmodernism school of legal philosophy produces a new school of "digimodernism" which is constantly developing and always in the process of dialecticization so that tracing the direction of its development requires a journey of thinking in the style of digitalization, breathing virtual but actually happening in legal reality. developed in human civilization. Keywords: Postmodernism, Digitalization, Digimodernism.